Analysis of Legal Protection for Women as Victims of Domestic Violence: Legal and Criminal Perspectives - Singgih, Nindia Kirana; Mahardhika, Vita (JSSH (Jurnal Sains Sosial dan Humaniora), 2025)
Domestic violence (DV) is a form of human rights violation that has a serious impact on women, both physically, psychologically, and socially. This study uses qualitative methods and normative law. The research approach uses a legislative approach and a conceptual approach and data obtained using secondary data through literature studies. The results of this study indicate that legal protection for victims of domestic violence needs to be integrated through an integrated service system, a victim-based approach, and the involvement of various legal, social, and psychological sectors. In the case study, the court has sentenced the perpetrator to prison as a form of law enforcement, but aspects of non-criminal protection such as rehabilitation and continued protection for victims are still not optimal.